Valuation of financial derivatives through transmutation operator methods - Kravchenko, Igor Viktorovich (2019)
Nowadays there is a fast development of the methods based on transmutation operators (TO) theory for solving differential equations. The possibility to construct the images of solutions for TO in certain cases allowed the construction of accurate numerical solutions to several problems that appear in different applied fields. In the present work, for the first time, it is shown that these methods can be effectively applied to the optimal stopping problems that appear in mathematical finance. The first part of the thesis (Chapter 2) consists of an application of the method to the valuation of European-style double-barrier knock-out options (DBKO). This is done by using the efficient computation of eigenvalues for the Shrodinger equation and a representation of solutions in terms of Neumann series of Bessel functions. This knowledge was used in the construction of a novel analytically tractable method for pricing (and hedging) DBKO, which can be applied to the whole class of one-dimensional timehomogeneous diffusions even for the cases where the corresponding transition density is not known. The proposed numerical method is shown to be efficient and simple to implement. To illustrate the flexibility and computational power of the algorithm it is constructed an extended jump to default model that is able to capture several empirical regularities commonly observed in the literature. The second part of the thesis (Chapters 3 and 4) is dedicated to the study of the more complicated problems: the free boundary problems. For this purpose, the method was first (in some certain sense) generalized and tested on the Stefan-like problem. The method consists in efficiently constructing a complete system of solutions for parabolic equation from known solutions for the heat equation, heat polynomials (HP). This way it was possible to extend the numerical method that existed only for the heat equation to the large class of parabolic equations. However, for the selected financial problem, Russian option with finite horizon (ROFH), the numerical computation from the method based on HP revealed to be non-efficient. This is due to the more complex structure of the problem, specifically the non-consistent boundary conditions. Hence, it was developed another variation of the method that uses different systems of solutions for the heat equation: the generalized exponential basis. The constructed method proved to be accurate, relatively easy to implement and can it can be applied to the large class of the free boundary problems. The value of the ROFH has been an important theme of discussion in the last decades. The application of the method to this problem confirmed several results that have appeared recently in the literature and shred some light on the differences that were present.The constructed methods have a large scope of applications not only in financial field, but also in other disciplines. Both studies also open a variety of future research and applications that are discussed in the text.